LITE-1 mediates behavioral responses to X-rays in Caenorhabditis elegans - Cannon, Kelli E.; Ranasinghe, Meenakshi; Millhouse, Paul W.; Roychowdhury, Ayona; Dobrunz, Lynn E.; Foulger, Stephen H.; Gauntt, David M.; Anker, Jeffrey N.; Bolding, Mark (Frontiers in Neuroscience, 2023)
Rapid sensory detection of X-ray stimulation has been documented across a wide variety of species, but few studies have explored the underlying molecular mechanisms. Here we report the discovery of an acute behavioral avoidance response in wild type C. elegans to X-ray stimulation. The endogenous C. elegans UV-photoreceptor protein LITE-1 was found to mediate the locomotory avoidance response. Transgenic expression of LITE-1 in C. elegans muscle cells resulted in paralysis and egg ejection responses to X-ray stimulation, demonstrating that ectopic expression of LITE-1 can confer X-ray sensitivity to otherwise X-ray insensitive cells. This work represents the first demonstration of rapid X-ray based genetically targeted (X-genetic) manipulation of cellular electrical activity in intact behaving animals. Our findings suggest that LITE-1 has strong potential for use in this minimally invasive form of neuromodulation to transduce transcranial X-ray signals for precise manipulation of neural activity in mammals, bypassing the need for invasive surgical implants to deliver stimulation.Here we report the discovery of LITE-1 dependent behavioral responses to X-radiation. Importantly, we show that LITE-1 can confer X-ray sensitivity when transgenically expressed in otherwise X-ray insensitive cells. This is the first demonstration of acute X-ray mediated modulation of cellular electrical activity that has similar functionality to optogenetics, but avoids the need for surgical implantation of optic fibers and improves targeting capabilities.